Youth Mental Health First‐Aid: Juvenile Justice Staff Training to Assist Youth with Mental Health Concerns. (5th March 2020) - Anderson, Robert; Treger, Jennifer; Lucksted, Alicia
Abstract: Many youth in juvenile justice settings meet criteria for a mental health condition. Front line staff need to be able to recognize and respond to their needs, but training is often lacking. Youth Mental Health First Aid (YMHFA) is an 8‐hour training for adults without mental health education to recognize and assist distressed youth. This study surveyed 1, 279 [State blinded] DJS front‐line staff trained in YMHFA. Of 338 returned surveys (26% response), 44% reported using YMHFA skills at work, 56% in preventing a crisis, 25% during crises. Respondents rated YMHFA as significantly improving their responsiveness to distressed young people.